2021
DOI: 10.3390/d13070286
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution Patterns of Appendicularians in the Drake Passage: Potential Indicators of Water Masses?

Abstract: Appendicularians are one of the most common animals found within zooplankton assemblages. They play a very important role as filter feeders but are, unfortunately, inconsistently reported in the Antarctic literature. The present paper attempts to describe the zonal diversity of appendicularians and the main environmental factors influencing their communities in the Drake Passage. Samples were collected during Antarctic summer in 2009–2010. A total of eight species of larvaceans were identified. Fritillaria bor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 55 publications
2
6
1
Order By: Relevance
“…Other species, i.e., F. antarctica, F. aberrans, O. fusiformis and O. parva had not been previously noted in the investigated region or in the entire area of the Antarctic Peninsula. However, we observed the presence of these species in the Drake Passage [16]. The larvacean abundance recorded in this study was higher than that found by Freire et al [27], i.e., 1200 ind.…”
Section: Appendicularians Diversity and Abundancecontrasting
confidence: 75%
See 4 more Smart Citations
“…Other species, i.e., F. antarctica, F. aberrans, O. fusiformis and O. parva had not been previously noted in the investigated region or in the entire area of the Antarctic Peninsula. However, we observed the presence of these species in the Drake Passage [16]. The larvacean abundance recorded in this study was higher than that found by Freire et al [27], i.e., 1200 ind.…”
Section: Appendicularians Diversity and Abundancecontrasting
confidence: 75%
“…Similar observations were made by Tsujimoto et al [20]. Daponte and Esnal [21] validated the Antarctic species of the "Oikopleura gaussica group" in the regions near South Georgia and in the Bellingshausen Sea, and Kalarus and Panasiuk [16] researched the zonal distribution of these animals in the Drake Passage. Most other studies conducted in recent decades have examined entire zooplankton communities and have examined appendicularians only as a single group or by focusing on the dominant species [22][23][24][25].…”
Section: Introductionsupporting
confidence: 79%
See 3 more Smart Citations